Advanced macroergonomics and sociotechnical approaches for optimal organizational performance - Realyvasquez, Arturo, 1984-; Maldonado-Macías, Aidé Aracely; Arredondo, Karina Cecilia, 1983- (Business Science Reference, 2018)
"This book explores macroergonomics topics and organizational strategies in different work fields. It also includes developing of new theories, applying specific macroergonomic methods, theories and studies for promoting the adoption of macroergonomics in different work systems around the world in order to achieve enhanced organizational practices in benefit of healthier work environments for human well-being"--